Integration of all‐printed zinc ion microbattery and glucose sensor toward onsite quick detections. Issue 3 (26th April 2022) - Jiang, Kang; Wen, Xi; Deng, Yuxian; Zhou, Zeyan; Weng, Qunhong
Abstract: Rational design of microsystems and efficient integration of various functional modules that can directly realize the aimed functions are very attractive for portable and onsite practical applications, which is also significant in developing miniaturized and intelligent electronics and equipment. Unlike the conventional electrochemical glucose sensors that always need auxiliary complex systems for power supply, signal processing, and feedbacks, we design an all‐printed glucose sensor integrated with a zinc ion microbattery (ZIMB) as a micropower source for portable and onsite quick glucose detections. The integrated glucose sensor (GS) and ZIMB (iGS‐ZIMB) system possesses a high areal energy density of 247.3 μWh/cm 2 and power density of 1193 μW/cm 2 and exhibits high sensitivity up to 464.2 μA/mM/cm 2, wide linear range of 0.5–6.0 mM, and good reproducibility in glucose detections. Through a simple amplification circuit design, the glucose concentration signals could be displayed within a short response time of 1.6 s without the need of external auxiliary equipment. Such iGS‐ZIMB microsystem has prominent advantages in efficiency and cost and is promising for onsite medical and healthcare applications. Abstract : A strategy of integrating a zinc ion microbattery for glucose sensor power supplying, and a simple amplifying circuit for signal feedbacks and displays are proposed, which realize simultaneous excellent electrochemical performances of GS and ZIMB in iGS‐ZIMB and onsite quick glucose detections, and may bring paradigm shifts in designs of modern microelectromechanical systems toward low‐cost, portable, and small‐scale microsystems.